Strategi Bersaing BMT Al Fataya Payakumbuh pada Era Keuangan Digital Syariah dengan Pendekatan SWOT Analisis - Vina Addila Putri; Indika Juang Putra; M. Imamuddin; Rini Elvira (STKIP Subang, 2026)
Digital transformation has driven significant changes in the Islamic financial industry, including microfinance institutions such as Baitul Maal wat Tamwil (BMT). This article aims to analyze the competitive strategy of BMT Al Fataya Payakumbuh in facing the dynamics of Islamic digital finance using a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The research was conducted using descriptive qualitative methods through observation, in-depth interviews, and documentation. The analysis results indicate that BMT Al Fataya possesses strengths such as a good reputation, member loyalty, and innovative Islamic products, but still faces weaknesses such as limited capital, a lack of digital talent, and slow technology adoption. Externally, opportunities arise from the growth of Islamic fintech, increasing public digital literacy, and potential technology partnerships, while the main threat comes from competition from large-scale Islamic financial institutions, rural banks (BPRs), and commercial banks. Recommended strategies include developing digital services (mobile banking and e-wallets), increasing human resource capacity, and promoting digital initiatives based on local communities. These findings emphasize the importance of collaboration, service innovation, and digital adaptation to strengthen BMT competitiveness in the modern Islamic financial era.